2010
DOI: 10.1002/clc.20721
|View full text |Cite
|
Sign up to set email alerts
|

Recurrence of Acute Myocardial Infarction in Patients Discharged on Clopidogrel and a Proton Pump Inhibitor After Stent Placement for Acute Myocardial Infarction

Abstract: Background: The purpose of this study was to determine the readmission rate for acute myocardial infarction (AMI) in patients discharged on clopidogrel and a proton-pump inhibitor (PPI) versus patients discharged on clopidogrel alone after experiencing an AMI and undergoing stent placement. Clopidogrel is a prodrug that requires metabolism in the liver by the cytochrome P450 system (CYP450), in particular cytochrome P450 2C19 (CYP2C19).1 Recent studies have suggested that medications metabolized by CYP450, suc… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
25
1
4

Year Published

2010
2010
2022
2022

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 51 publications
(30 citation statements)
references
References 21 publications
0
25
1
4
Order By: Relevance
“…As shown in Table 3, there is inconsistency among these studies' conclusions. Twenty found a statistically significant association of PPI use and worse CV outcomes in patients on clopidogrel [2][3][4][5]60,[62][63][64]66,68,69,71,74,77,78,82,[85][86][87][88] ; of the other 15, one did not report the level of statistical significance, 84 and 14 found no evidence of an association. 6,7,38,39,57,58,65,70,76,[79][80][81]83,89 Eight systematic reviews published within 2010 have examined this association, 28,90-96 and 5 have attempted a meta-analysis of the results (Table 4).…”
Section: Interaction Between Ppis and Clopidogrelmentioning
confidence: 99%
See 1 more Smart Citation
“…As shown in Table 3, there is inconsistency among these studies' conclusions. Twenty found a statistically significant association of PPI use and worse CV outcomes in patients on clopidogrel [2][3][4][5]60,[62][63][64]66,68,69,71,74,77,78,82,[85][86][87][88] ; of the other 15, one did not report the level of statistical significance, 84 and 14 found no evidence of an association. 6,7,38,39,57,58,65,70,76,[79][80][81]83,89 Eight systematic reviews published within 2010 have examined this association, 28,90-96 and 5 have attempted a meta-analysis of the results (Table 4).…”
Section: Interaction Between Ppis and Clopidogrelmentioning
confidence: 99%
“…Table 3 summarizes 41 studies that assessed whether coadministration of 1 or more PPIs affects clinical outcomes in patients on clopidogrel. [2][3][4][5][6][7]38,39, Only 2 were randomized controlled trials (RCTs), 39,58 another 2 were posthoc analyses of data from previous RCTs that had been designed to address a different question, 39,58 [2][3][4][5][6][7]38,39,57,58,60,[62][63][64][65][66][68][69][70][71]74,[76][77][78][79][80][81][82][83][84][85][86][87][88][89]. As shown in Table 3, there is inconsistency among these studies' conclusions.…”
Section: Interaction Between Ppis and Clopidogrelmentioning
confidence: 99%
“…However, in a stratified analysis, pantoprazole, which does not inhibit CYP2C19, was not associated with readmission (adjusted OR: 1.02; 95%CI = 0.70–1.47); the adjusted OR for other PPIs was 1.40 (95%CI = 1.10–1.77). Other studies have revealed that esomeprazole [37] and omeprazole [31] are associated with adverse outcomes of clopidogrel therapy, likely because of their potent inhibition of CYP2C19 [38]. Interestingly, in the COGENT randomized controlled study [38] of patients with ACS or undergoing placement of a coronary stent, there was no difference in the effects of a fixed‐dose combination of clopidogrel (75 mg) with omeprazole (20 mg) or clopidogrel alone (both groups also used aspirin at 75–325 mg/day) on the cardiovascular endpoint (a composite of cardiovascular death, nonfatal MI, CABG or PCI or ischemic stroke; HR = 1.02, 95%CI = 0.70–1.51).…”
Section: What Is Clopidogrel Resistance?mentioning
confidence: 99%
“…After 1 month, omeprazole group had significantly more nonresponders according VASP assay than pantoprazole group (44% vs. 23%; p<0.05). However, clinical impact of this interaction was unclear and has been evaluated in number of observational studies with often conflicting conclusion [69][70][71][72]. The only randomized controlled trial assessing the clinical impact of this interaction was the COGENT trial [73].…”
Section: Medications Interactionsmentioning
confidence: 98%